Pelatihan Kewirausahaan Berbasis Pemanfaatan Bahan Pangan Lokal bagi Anggota PKK di Ngestiharjo Kabupaten Bantul - Esti Setiawati; Salamah Salamah; Sukadari Sukadari (Jurnal Pengabdian UNDIKMA, 2023)
The purpose of this community service is to improve the entrepreneurial skills and motivation of PKK mothers through the use of local food ingredients in Cungkuk Ngestiharjo, Bantul Regency. The method of implementing this community service activity is training consisting of banana chip processing activities, product packaging, and social media-based marketing. Meanwhile, the evaluation instrument for this activity uses a questionnaire and is analyzed descriptively. The results of the community service show that PKK members: 1) are able to make products that have economic value in the form of banana chips snacks; 2) motivated to be self-employed so as to improve the family economy, 3) able to package attractive and safe products, and 4) able to market snack products through social media.